The Kentucky River - Ellis, William E. (William Elliott), 1940- (Book collections on Project MUSE., 2000)
"Beginning with an intriguing overview of the river's formation and characteristics, Ellis shows how the stream has helped shape Kentucky's environment, economy, and political culture. In centuries past, flotillas of flatboats carried whiskey, pork, and valuable raw materials downriver to markets in Louisiana. Later, the river became a source of entertainment as showboats brought theater, movies, music, and dancing to otherwise isolated communities."